2021
DOI: 10.3389/feduc.2020.592870
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study on the Use of Contexts and Socio-Scientific Issues-Based Science Education by Pre-service Junior High School Science Teachers in Indonesia During Their Final Year Teaching Internship

Abstract: This paper presents a case study looking at the use of daily life contexts and socio-scientific issues by pre-service science teachers (PSTs) in Indonesia during their final year teaching internship. The study is based on a questionnaire distributed to 42 PSTs at a State University in East-Java after they took part in a teaching internship program. The questionnaire focuses on the contexts the PSTs used in their teaching and how the contexts were used. Additionally, eight of the PSTs who taught a unit on envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The same result was concluded in the study of Sibic and Topcu (2020) where more than 50% of the participants were aware of the SSIs before they conducted their investigation. In contrast, some studies revealed that the number of teachers who had never read or heard about SSI-based teaching exceeded those who had previous knowledge about it (Öztürk & Erabdan, 2019;Eilks et al, 2020). Meanwhile, Sadler, Amirshokoohi, Kazempour and Allspaw (2006) mentioned that for effective SSI teaching to happen in classrooms, it is necessary that science teachers are not just aware of it but also know what SSI is and how it contributes to the aims of science education.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The same result was concluded in the study of Sibic and Topcu (2020) where more than 50% of the participants were aware of the SSIs before they conducted their investigation. In contrast, some studies revealed that the number of teachers who had never read or heard about SSI-based teaching exceeded those who had previous knowledge about it (Öztürk & Erabdan, 2019;Eilks et al, 2020). Meanwhile, Sadler, Amirshokoohi, Kazempour and Allspaw (2006) mentioned that for effective SSI teaching to happen in classrooms, it is necessary that science teachers are not just aware of it but also know what SSI is and how it contributes to the aims of science education.…”
Section: Discussionmentioning
confidence: 99%
“…The instrument, "Questionnaire on Teachers' Awareness, Need, Readiness and Willingness on the Implementation of SSI-based Approach" was a researcher-made questionnaire. It was an online questionnaire in a Google form format designed to obtain information about (a) the demographic profile of the teachers and (b) teachers' awareness, perceived need, readiness and willingness tailored from the study of Eilks et al (2020). The questionnaire was subjected to face and content validation before it was disseminated online.…”
Section: Instrument and Data-gathering Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the analysis of the implementation of SSI-based science education around the world by Genisa et al, it is concluded that the implementation of SSI-based science education is mostly conducted in developed countries, including the United States, Germany, Sweden, or Japan, and it is only infrequently implemented in Indonesia. , Some of the reasons for the lack of SSI-based science education in Indonesia are limited teacher knowledge about SSI-based science education and very little experience in its application. , Science teachers in Indonesia tend not to focus on the controversial nature of SSIs when they teach. Teachers, nevertheless, acknowledge that SSIs might have great potential for engaging students in science class . These studies suggest a need to incorporate SSI-based science education more thoroughly in general, and in science teacher education programs in Indonesia in particular.…”
Section: Introductionmentioning
confidence: 99%
“…Teachers, nevertheless, acknowledge that SSIs might have great potential for engaging students in science class. 29 These studies suggest a need to incorporate SSI-based science education more thoroughly in general, and in science teacher education programs in Indonesia in particular.…”
Section: ■ Introductionmentioning
confidence: 99%